Factors Influencing the Adaption of Online Pharmacy in Oman: Pilot Study - Alsideiri A.; Cob Z.B.C.; Drus S.B.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Behavioral research; Covariance matrix; Digital storage; Testing; Cutting edges; Hold up; Information and communication; Online pharmacies; Personal development; Pilot studies; Technology acceptance model; Technology adoption; UTAUT2; Value-added information; Surveys